Effect of Thermal Barrier Coating on the Thermal Stress of Gas Microturbine Blades and Nozzles - Tenango-Pirin, Oscar (2020)
Thermal barrier coatings play a key role in the operational life of microturbines because they reduce thermal stress in the turbine components. In this work, numerical computations were carried out to assess new materials developed to be used as a thermal barrier coating for gas turbine blades. The performance of the microturbine components protection is also evaluated. The new materials were 8YSZ, Mg2SiO4, Y3Ce7Ta2O23.5, and Yb3Ce7Ta2O23.5. For testing the materials, a 3D gas microturbine model is developed, in which the fluid-structure interaction is solved using CFD and FEM. Temperature fields and stress magnitudes are calculated on the nozzle and blade, and then these are compared with a case in which no thermal barrier is used. Based on these results, the non-uniform temperature distributions are used to compute the stress levels in nozzles and blades. Higher temperature gradients are observed on the nozzle; the maximum temperature magnitudes are observed in the blades. However, it is found that Mg2SiO4 and Y3Ce7Ta2O23.5 provided better thermal insulation for the turbine components compared with the other evaluated materials. Mg2SiO4 and Y3Ce7Ta2O23.5 presented the best performance regarding stress and thermal insulation for the microturbine components.